2007
DOI: 10.1007/s10856-006-0103-0
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, microstructure and mechanical properties of porous titanium sintered by Ti fibres

Abstract: Open-cell porous Ti with a porosity ranging from 35 to 84% was successfully manufactured by sintering titanium fibres. The microstructure of the porous titanium was observed by SEM and the compressive mechanical properties were tested. By adjusting the spiral structure of the porous titanium, the pore size can be controlled in a range of 150-600 microm. With the increasing of the porosity, compressive yield strength and modulus decrease as predicated. However, high mechanical properties were still obtained at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…The plastic and elastic collapse models for compressive stresses of foams can be combined using the rule of mixture to calculate the plateau stress of the foam [40]:…”
Section: Ab Cmentioning
confidence: 99%
See 1 more Smart Citation
“…The plastic and elastic collapse models for compressive stresses of foams can be combined using the rule of mixture to calculate the plateau stress of the foam [40]:…”
Section: Ab Cmentioning
confidence: 99%
“…It also depends on the pores' size, shape and distribution, including detailed pore morphology, such as micro-pores forming at the edges [42].A s underlined in Ref. [40], pore shapes and sizes play a critical role in determining the compression behaviors of foams. In Ref.…”
Section: Young's Modulusmentioning
confidence: 99%
“…Zou et al reported that the compressive yield strengths of sheaved titanium fiber sheets with a porosity of 53, 67, and 72% were approximately 200, 100, and 60 MPa, respectively 26) . Conversely, the compressive strengths of commercially available bone ceramics with a porosity of 0.93 and 53% were 33.9 and 0.24 MPa, respectively 27) .…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the fiber volume fraction, the network architecture (isotropic or highly oriented), and the fiber segment aspect ratio, experimentally measured Young's moduli values are no higher than a few GPa. [15][16][17][18][19] The elastic properties of highly porous materials are most commonly measured using conventional mechanical (static) testing with the majority of studies focusing on compressive testing as it is easier to carry out compared with tensile testing or even bending. However, it is well known that in highly porous materials inelastic straining commonly occurs at low applied loads.…”
Section: Introductionmentioning
confidence: 99%